Measuring the relationship between social capital, race, and education - Contreras, Jennifer; Amissah, Christopher M.; Khademi, Abdolvahab; Valeriann, Christine; Villalonga-Olives, Ester (Frontiers in Public Health, 2025)
Enhancing social and community support (e.g., social capital) is essential for building healthier communities, as social capital significantly influences health outcomes. However, the relationship between social capital, race, and education is complex. Historically marginalized groups often face systemic barriers that reduce their social capital. Therefore, longitudinal research is essential to understand these dynamics and address health disparities. This study explores the relationship between social capital, race, and education in U.S. adults over time, using Midlife in the U.S. (MIDUS) data from Waves 1–3 (1995–1996; 2004–2006; 2013–2014). We used the disparity assessment framework from Ward et al. and multilevel mixed-effects models to investigate how social capital evolved differently based on race and education as well as the potential implications of these differences. Our findings revealed that Black respondents consistently demonstrated higher community contributions and community involvement compared with White respondents, despite having lower education on average. This social capital advantage for Black respondents persisted across all three waves of the MIDUS study. Longitudinal analysis also showed that community contributions remained stable at all time points for all respondents, while community involvement declined at MIDUS 3. However, Black respondents exhibited a prominent increase in community involvement at MIDUS 3, suggesting that Black communities may have adapted and thrived through culturally specific forms of social capital during that period. Our findings indicated these positive manifestations of social capital should be explored to see how it can be supported and suggested the need for further exploration of racial dynamics and culturally specific forms of social capital.